2019
DOI: 10.1093/ofid/ofz292
|View full text |Cite
|
Sign up to set email alerts
|

Erythema Migrans: Course and Outcome in Patients Treated With Rituximab

Abstract: Background Information on Lyme borreliosis (LB) in patients treated with rituximab is limited to individual case reports. Methods We reviewed data on adult patients diagnosed with typical erythema migrans (EM) at the LB outpatient clinic of the University Medical Center Ljubljana, Slovenia, in the 10-year period 2008–2017. For all patients, clinical and laboratory information was acquired prospectively using a standardized qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 25 publications
0
3
0
1
Order By: Relevance
“…The second characteristic of this case is, unlike the Tick-borne Relapsing Fever Borrelia species, spirochete visualization on blood smears is very rare for members of the B burgdorferi complex (except for B mayonii) , which testifies to the intensity of the bacterial load in this patient, estimated at 4 bacteria per 10 0 0 erythrocytes ( Jakab et al, 2022 ;Pritt et al, 2016 ). B garinii can nevertheless be isolated in blood culture (in ∼1% of cases) and particularly in patients treated with rituximab ( Maraspin et al, 2019 ). The patient's immunosuppressed status may have favored a high-grade bacteremia and the spread of the infection.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The second characteristic of this case is, unlike the Tick-borne Relapsing Fever Borrelia species, spirochete visualization on blood smears is very rare for members of the B burgdorferi complex (except for B mayonii) , which testifies to the intensity of the bacterial load in this patient, estimated at 4 bacteria per 10 0 0 erythrocytes ( Jakab et al, 2022 ;Pritt et al, 2016 ). B garinii can nevertheless be isolated in blood culture (in ∼1% of cases) and particularly in patients treated with rituximab ( Maraspin et al, 2019 ). The patient's immunosuppressed status may have favored a high-grade bacteremia and the spread of the infection.…”
Section: Discussionmentioning
confidence: 85%
“…First, the patient developed an original clinical presentation mimicking high-grade lymphoma transformation, whereas B garinii infection usually presents as a classical Lyme disease with a neurological tropism ( Steere et al, 2016 ;Strle and Stanek, 2009 ). In the literature, immunocompromised patients present more disseminated erythema migrans with multiple lesions or extracutaneous manifestation ( Maraspin et al, 2019( Maraspin et al, , 2006. Neuroborreliosis is difficult to diagnose in these patients, especially those receiving rituximab; indeed, serology is often negative due to their hypogammaglobulinemia: PCR is then crucial for the diagnosis ( Harrer et al, 2007 ;van Dop et al, 2013 ;Wagemakers et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Findings in the control group are in accord with our recent report on EM in immunocompetent adult patients, in which similar approaches were used to assess the course and outcome of EM as in the present study: median time to resolution of EM was 7 days, and the time showed significant prolongation with advancing age; in 11/1176 (0.9%) patients residual erythema could still be seen at the 2–3 month visit [33]. In our previous reports on immunocompromised patients median durations of EM after the beginning of antibiotic treatment were 6 days for patients with solid organ transplantation [8], 7 days for patients having haematological malignancy [10], and 12 days for patients treated with rituximab [34], while the proportions of patients with still visible EM at a visit 2–3 months after institution of antibiotic treatment were 1/6 (17%), 1/53 (1.9%), and 1/7 (14.3%), respectively [8,10,34].…”
Section: Discussionmentioning
confidence: 99%
“…На сегодняшний день отсутствуют данные о том, что БЛ, развившаяся во время беременности, приводит к врождённой инфекции или синдрому врождённых аномалий плода, в связи с чем выходящее за рамки стандартных схем дополнительное лечение или наблюдение за матерью или ребёнком не рекомендуется. Пациенты с ослабленной иммунной системой успешно лечились от БЛ с использованием схем, изученных на исходно здоровом макроорганизме [5][6][7].…”
Section: Introductionunclassified